Comparison of the intensity of peripheral inflammation between major depressive disorder and bipolar depression by means of neutrophil-lymphocyte and platelet-lymphocyte ratios: The possible role of clinical severity and psychotic features - YORGUNER, NEŞE (My University, 2022)
Objective: The present study aimed to compare the intensity of inflammation between major depressive disorder (MDD) and bipolar disorder-depressive episode (BD-D) by using neutrophil to lymphocyte (NLR) and platelet to lymphocyte ratios (PLR) as nonspecific markers for peripheral immune response, and to investigate whether and how these parameters correlate with the clinical characteristics of the depressive episodes within and between the diagnoses. Patients and Methods: The medical records of 209 psychiatric inpatients (126 diagnosed with MDD, 83 with BD-D) and 150 healthy controls (HC) were retrospectively screened to obtain NLR and PLR values. Results: Both MDD and BD-D presented with significantly elevated NLR and PLR compared to HC, with the increase being associated with the severity of depression but not with the presence of psychotic features. The severity of inflammation was found to be of a comparable magnitude between the two conditions, or at least indistinguishable by means of the NLR and PLR. Conclusion: Our results suggest that both MDD and BD-D involve a presumably complex inflammatory process resulting in an observable, albeit nonspecific alteration in the distribution of peripheric blood cells. Moreover, the magnitude of the observed immune response appears to relate to the severity of the depressive episode for both conditions.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Major depressive disorder; Bipolar disorder; Inflammation; Immune dysregulation; Neutrophil-lymphocyte ratio; Platelet-lymphocyte ratio; C-REACTIVE PROTEIN; UNIPOLAR DEPRESSION; NEUTROPHIL/LYMPHOCYTE RATIO; PROINFLAMMATORY MARKERS; SCHIZOPHRENIA; ADIPONECTIN; CYTOKINES; SUBTYPES; STRESS; SYSTEM; Major depressive disorder; Bipolar disorder; Inflammation; Immune dysregulation; Neutrophil-lymphocyte ratio; Plateletlymphocyte ratio